Biofilm and planktonic microbial communities in highly acidic soil (pH < 3) in the Soos National Nature Reserve, Czech Republic - Hujslová, Martina; Gryndlerová, Hana; Bystrianský, Lukáš; Hršelová, Hana; Gryndler, Milan (Extremophiles, 2020)
Biofilm formation is a typical life strategy used by microorganisms populating acidic water systems. The same strategy might be used by microbes in highly acidic soils that are, however, neglected in this regard. In the present study, the microbial community in such highly acidic soil in the Soos National Nature Reserve (Czech Republic) has been investigated using high-throughput DNA sequencing and the organisms associated with biofilm life mode and those preferring planktonic life were distinguished using the biofilm trap technique. Our data show the differences between biofilm and planktonic microbiota fraction, although the majority of the organisms were capable of using both life modes. The by far most abundant prokaryotic genus was Acidiphilium and fungi were identified among the most abundant eukaryotic elements in biofilm formations. On the other hand, small flagellates from diverse taxonomical groups predominated in plankton. The application of cellulose amendment as well as the depth of sampling significantly influenced the composition of the detected microbial community.
Keywords: půdní mikrobiologie; Česká republika; mikrobiota; biofilmy; Soil; plankton; půda; Microbiota; Plankton; koncentrace vodíkových iontů; Biofilms; Hydrogen-Ion Concentration; Czech Republic; Soil Microbiology